2023
DOI: 10.1039/d3sc05263j
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical halogen-bonding assisted carbothiophosphorylation reactions of alkenyl and 1,3-dienyl bromides

Helena F. Piedra,
Victoria Gebler,
Carlos Valdés
et al.

Abstract: The photochemical halogen-bonding assisted alkenylation and dienylation of phosphoro(di)thioate diesters under batch and continuous flow is disclosed. Mechanistic studies support the formation of the halogen-bonding complex and the radical pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Additionally, a high quantum yield but yet below the unit (φ = 0.9) was determined for the transformation (see the SI for a detailed description), which could point at radical chain propagation events, but we believe may be mainly attributed to the high efficiency of these processes. [28] Considering both of these experiments and also taking into account our previous experience in similar photochemical HaB assisted alkenylation reactions, [10] we believe that radical chain propagation events are unlikely to take place in this reaction. At the same time, the importance of light for the reaction to proceed was validated.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, a high quantum yield but yet below the unit (φ = 0.9) was determined for the transformation (see the SI for a detailed description), which could point at radical chain propagation events, but we believe may be mainly attributed to the high efficiency of these processes. [28] Considering both of these experiments and also taking into account our previous experience in similar photochemical HaB assisted alkenylation reactions, [10] we believe that radical chain propagation events are unlikely to take place in this reaction. At the same time, the importance of light for the reaction to proceed was validated.…”
Section: Resultsmentioning
confidence: 91%
“…In light of all these mechanistic studies, and also based on our previous experience in photochemical halogen-bonding assisted alkenylation reactions, [10] we propose the mechanism depicted in scheme 5 for the cross-coupling reaction between alkenyl or dienyl bromides and sodium sulfinates 2. First, the formation of a HaB complex 6 between 1 (or 4) and 2 is hypothesized, which would be photoexcited with blue light, causing its fragmentation through reduction of the CÀ Br bond in an intermolecular photoinduced electron transfer (PET) event.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Against this backdrop, research has focused on radical generation methods based on halogen bonding, which is a noncovalent interaction. , Halogen bonding involves electrostatic interactions between a positively charged region known as the sigma hole on a halogen atom and a Lewis base . Conventionally, mechanisms similar to those of a Lewis acid are commonly used to harness this interaction. , However, recent studies have revealed that upon irradiating complexes formed through halogen bonding with appropriate light, photoinduced electron transfer occurs within organic molecules, leading to the generation of various corresponding carbon radical species, including alkyl, aryl, and alkenyl radicals (Scheme d).…”
mentioning
confidence: 99%